Desenvolvimento de métodos simples e rápidos para determinação de fármacos por eletroforese capilar com detecção condutométrica sem contato (CE-C4D) - Marra, Mariana Cardoso (2018)
In this work, capillary electrophoresis with capacitively coupled contactless conductivity detection (CE-C4D) was used for the development of fast methods for determination of active principles in pharmaceutical samples. The background electrolyte (BGE) composed of 10 mmol L-1 of TRIS and 10 mmol L-1 of TAPS (pH 8.4) was used for the analysis of pharmaceutical formulations containing: amoxicillin (AMX) + clavulanate (CLA) + potassium (K). Another BGE composed of 10 mmol L-1 of boric acid ajusted with sodium hydroxide (pH = 9) was used for the analysis of pharmaceutical samples containing: (a) hydrochlorothiazide (HCT) + losartan (LOS) + potassium (K); (b) HCT + atenolol (ATE); (c) HCT + metoprolol (MET); (d) HCT + propranolol (PRO); (e) HCT + valsartan (VAL); (f) HCT + benazepril (BEN); (g) HCT + captopril (CAP); (h) HCT + enalapril (ENA); (i) HCT + lisinopril (LIS); (j) HCT + ramipril (RAM). All proposed analytical methods are fast with duration less than 1 minute and presented low relative standard deviations in relation to peak area (< 4.6%) and migration times (< 1.7%), as well as adequate resolutions (> 1.3) between the analytical signals of each species. Calibration curves for all quantified species showed correlation coefficients greater than 0.995. The proposed methods showed the following limits of detection (LOD / μmol L 1): AMX = 25, CLA = 5, K = 4 (KCLA), HCT = 10, LOS = 3, K = 4 (KLOS), ATE = 3, MET = 4, PRO = 5, VAL = 14, BEN = 5, CAP = 7, ENA = 5, LIS = 5 and RAM = 6. The results obtained with the proposed method for analysis of commercial pharmaceutical samples containing AMX+CLA+K and HCT+LOS+K were compared with those obtained by HPLC and flame photometry (K). The calculated t-values (paired t-Student test), with confidence level of 95%, were smaller than the critical value (4.303, n = 3) in all the analyses, which indicates that there were no significant differences between the results found with the proposed method and HPLC. The proposed methods presented satisfactory results in the recovery test (92% to 106%). Furthermore, the methods are simple, low cost (equipment and maintenance), generate a minimum amount of waste (green analytical methods), and have a high analytical frequency (> 75 injections h-1).